Nitrate availability in Brazilian soils under effect of liming and sources and amounts of nitrogen - Silva, Carlos Alberto; do Vale, Fabiano Ribeiro (Pesquisa Agropecuaria Brasileira, 2000)
The aim of this work was to evaluate the effect of liming and sources and doses of nitrogen on nitrate availability in Brazilian soils. Two experiments were carried out: one with five soils from Bahia State and the other with five soils from Minas Gerais State. Soil samples were previously moistened and incubated at 26°C in order to activate the microorganism population. Soil samples from Bahia State were incubated with 50, 100, 150 e 200 mg of N per kg of soil as ammonium sulfate or urea and in the Minas Gerais soils it was evaluated the effect of liming on nitrification. Soil samples were incubated at 26°C during 15 days. Urea nitrified faster than ammonium sulfate. The sandy soil did not exhibit net nitrification following ammonium application, but nitrification in this soil was significantly higher under urea. The nitrate availability increases with the liming of Minas Gerais soils. Nitrification rate showed to be highly correlated with base saturation whereas urea hydrolysis was correlated with organic matter content.